Treponema pallidum induces the polarization of macrophages via macrophage-derived exosomes - Chunchan ZHENG; Jiahao XIE; Ruitao ZOU; Guiyue CAI; Sujun LUO; Na WEI; Sirui LI; Rongyi CHEN (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2022)
Objective To explore the effect of Treponema pallidum (Tp) -induced exosomes (EXOTp) by macrophages on macrophage polarization. Methods Human monocyte-macrophages (THP-1) were induced into macrophages, followed by stimulation with or without Tp for 24 h. After changing medium, cells were cultured for additional 48 h. The macrophage exosome suspension was collected, and exosomes were isolated by differential speed centrifugation. Isolated exosomes were identified by both Western blotting and transmission electron microscopy, and were quantitated with nanoparticle tracking technology. The internalization of the macrophages in the two groups was observed under a laser confocal microscope. In the experimental group, the isolated EXOTp was incubated with M0 macrophages for 24 h. Incubation of M0 macrophages with exosomes produced by non-Tp-treated macrophages served as negative controls, while M0 macrophages incubated without exosomes served as blank controls. At 6,12, and 24 h, the expression levels of INOS, IL-12, Arg-1, IL-10 and other mRNAs in all three groups were detected by qRT-PCR. Flow cytometry was used to identify macrophage phenotypes using MHC-Ⅱ, CD86, CD206, and CD209 markers. Results qRT-PCR showed that the expression levels of INOS and IL-12 mRNA in experimental group were time-dependently up-regulated (P<0.05), while expression levels of Arg-1 and IL-10 were not significantly changed. Moreover, expression levels of INOS, IL-12, Arg-1, and IL-10 mRNA were not significantly altered in the negative controls (P>0.05). Flow cytometry results showed that MHC-Ⅱ was positive (P<0.05), but the changes in CD86, CD206, and CD209 were not significant (P>0.05). Conclusions The exosomes secreted by THP-1-derived macrophages cannot induce the polarization of M0 macrophages to M1 macrophages. Upon the stimulation with Tp, the exosomes secreted by THP-1-derived macrophages can induce polarization of M0 macrophages to M1 macrophages.